Emergência, crescimento inicial de plântulas e enxertia hipocotiledonar por garfagem no topo em fenda cheia com miniestacas apicais para diferentes passifloráceas - Tiradentes, Aristhotelis Tadeu (2011)
Passion fruit is composed of about 630 species, which include economically three species: Passiflora edulis Sims f. flavicarpa, Passiflora alata and Passiflora edulis. Considering that their culture is prominent in South America with about 90% of world pr